Variasi perilaku mencari makan pada semut rangrang Oecophylla smaragdina (Fabricius) pada habitat yang berbeda: Variations of foraging behavior of weaver ants Oecophylla smaragdina (Fabricius) in different habitats - Rezki, Rezki; Aoliya, Nur; Fadliansyah, Fadliansyah; Wulandari, Siti Latifa; Jesajas, David Reinhard; Raffiudin, Rika (Perhimpunan Entomologi Indonesia, 2023)
Weaver ants (Oecophylla smaragdina (Fabricus)) are carnivorous insects and play a role as biocontrol agents in urban habitats. This study aims to analyze the foraging behavior of O. smaragdina in two different habitats, namely urban and non-urban. The two locations are characterized by differences in the intensity of human interaction and the distance between the trees and the tree canopy. The behavioral observation method uses all sampling events with five behavioral categories: lurking (M1), approaching (M2), carrying (M3), communicating between ants in a colony (K1), and competition with other ants (K2). We tested three different types of feed: chick scraps, Tenebrio molitor Linnaeus larvae, and sugar. The results showed that there were three sequences of foraging behavior in urban areas, namely: (1) M1, M2, K1, M3, (2) M1, M2, K1, M3, K2, and (3) M1, M2, K2, M3. Meanwhile, there is only one pattern in non-urban areas, namely M1, M2, M3. Approaching food (M2) and lurking food (M1) were the dominant responses of O. smaragdina in urban and non-urban areas. In urban areas, broiler chickens were the type of feed most approached by ants, followed by sugar and beetle larvae. O. smaragdina in non-urban areas also preferred chicken pieces as feed compared to the others, but only one individual O. smaragdina approached (M2) chicken pieces and none approached the others. Foraging ants are more active at high temperature and low humidity, compared to low temperature and high humidity. Therefore, the foraging behavior of O. smaragdina is influenced by habitat factors.